A Note on Greek τύραννος, pp. 245–250 - Rosół, Rafał (Polskie Towarzystwo Filologiczne, 2022)
This paper throws new light on the debate about the etymology of Greek τύραννος‘ absolute ruler, monarch, tyrant’. The author puts forward a hypothesis that it was borrowed indirectly from Hurrian šarrini- ‘~ the king’. This is a so-called determined form of the noun šarri- ‘king’, borrowed, in turn, from Akkadian šarru ‘id.’. Another word that goes back to Hurrian šarrini- is Biblical Hebrew/Philistine seren (attested in pl. sarnê or srānîm) ‘Philistine ruler’.